2014
DOI: 10.1021/pr5008202
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, Immune, and Gut Microbial Signals Mount a Systems Response to Leishmania major Infection

Abstract: leishmaniasis in humans, a neglected tropical disease that is difficult to manage. To understand the determinants of pathology, we studied L. major infection in two mouse models: the self-healing C57BL/6 strain and the nonhealing BALB/c strain. Metabolic profiling of urine, plasma, and feces via proton NMR spectroscopy was performed to discover parasite-specific imprints on global host metabolism. Plasma cytokine status and fecal microbiome were also characterized as additional metrics of the host response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…In the field of parasitic infections, this approach has shown capacity for characterising infection-induced metabolic changes in the host, within infected tissues and systemically (as measured by plasma or urine profiles). As yet, parasitic metabolic profiling studies have largely focused on in vitro assays [ 8 10 ] and experimental rodent models [ 11 15 ]. There have been very few examples of identifying the metabolic signature of a specific parasitic infection in humans [ 16 ], largely because human profiles are confounded by strong genetic and environmental variation, and are often superimposed upon a background of other concurrent endemic infections.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of parasitic infections, this approach has shown capacity for characterising infection-induced metabolic changes in the host, within infected tissues and systemically (as measured by plasma or urine profiles). As yet, parasitic metabolic profiling studies have largely focused on in vitro assays [ 8 10 ] and experimental rodent models [ 11 15 ]. There have been very few examples of identifying the metabolic signature of a specific parasitic infection in humans [ 16 ], largely because human profiles are confounded by strong genetic and environmental variation, and are often superimposed upon a background of other concurrent endemic infections.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that local cytokine production was specifically linked to skin microbiota. In a different study, L. major infection altered the gut microbiota of infected animals (but differently depending on mouse strain) (Lamour et al, 2015). Infection changed how gut microbiota correlated with systemic functions such as urine metabolites, plasma metabolites, and the immune system.…”
Section: Protozoan Infection Experiments Are Influenced By Microbiotamentioning
confidence: 95%
“…Moreover, differences in leishmaniasis disease outcome between different mouse strains (with C57BL/6 being self‐limiting and BALB/c progressing to more severe disease) have recently been associated with their specific microbial and metabolic profiles. Investigators attributed their distinctly differing metabolic profile to the ratios of two main classes: Clostridia and Gammaproteobacteria, with the former being more pronounced in the nonhealing BALB/c strain and the latter in C57/BL6 mice (Table ). This suggests that while differences in the course of infection are mainly attributed to genetic factors involving distinct immune responses as shown by the previous literature, the microbiome may play just as significant a role in the outcome of the infection.…”
Section: Parasites and The Microbiotamentioning
confidence: 99%